Active fault-tolerant tracking control for discrete-time switched LPV system based on virtual actuator method. Issue 6 (2022) - Che, Junxing; Liao, Fang; Zhu, Yanzheng; Basin, Michael V.; Zhou, Donghua
Abstract: In this paper, the active fault-tolerant tracking control issue is studied for a class of discrete-time switched linear parameter varying system by using the virtual actuator approach. First, a switched gain-scheduled virtual actuator is proposed to improve the faulttolerance performance. Second, in order to obtain better tracking performance, a sub-optimal trajectory recovery target is determined by minimizing the H∞ -norm of the virtual actuator's relevant transmission channel. By using the multiple parameter-dependent Lyapunov function approach, sufficient conditions for the tracking closed-loop system and virtual actuator system to be globally uniformly exponentially stable are derived, which also guarantee the desired H∞ performance indices requirement. Finally, effectiveness and applicability of the developed approaches are validated via a GE-90 turbofan-engine model system